2007
DOI: 10.1111/j.1440-1681.2007.04692.x
|View full text |Cite
|
Sign up to set email alerts
|

Actions of the Endocannabinoid Transport Inhibitor Am404 in Neuropathic and Inflammatory Pain Models

Abstract: 1. Although cannabinoid receptor agonists have analgesic activity in chronic pain states, they produce a spectrum of central cannabinoid CB(1) receptor-mediated motor and psychotropic side-effects. The actions of endocannabinoids, such as anandamide, are terminated by uptake and subsequent intracellular enzymatic degradation. In the present study, we examined the effect of acute administration of the anandamide transport inhibitor AM404 in rat models of chronic neuropathic and inflammatory pain. 2. Systemic ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 43 publications
2
26
0
Order By: Relevance
“…This anti-allodynic effect was blocked by the CB 2 receptor antagonist, SR144528, but not by rimonabant. In addition, AM404 blocked mechanical allodynia in rats subjected to partial nerve ligation (53). This effect was blocked by a CB 1 receptor antagonist; however, CB 2 receptor antagonists were not evaluated in this study.…”
Section: Neuropathic Painmentioning
confidence: 75%
“…This anti-allodynic effect was blocked by the CB 2 receptor antagonist, SR144528, but not by rimonabant. In addition, AM404 blocked mechanical allodynia in rats subjected to partial nerve ligation (53). This effect was blocked by a CB 1 receptor antagonist; however, CB 2 receptor antagonists were not evaluated in this study.…”
Section: Neuropathic Painmentioning
confidence: 75%
“…HögestĂ€tt et al (2005) have shown that the intermediate paracetamol metabolite, p-aminophenol, is converted in the brain into the novel metabolite AM404 through the action of FAAH (HögestĂ€tt et al, 2005). Before that, AM404 has been shown to induce analgesia (La Rana et al, 2006;Borsani et al, 2007;Mitchell et al, 2007) hypothermia at high doses in rats (Rawls et al, 2006). AM404 also acts as an activator of the TRPV1 channel (De Petrocellis et al, 2000) and inhibits COX-1 and COX-2 activities (HögestĂ€tt et al, 2005).…”
Section: Paracetamol-induced Hypothermia and Am404mentioning
confidence: 99%
“…Our study might suggest that compounds capable to prolong the lifespan of anandamide by inhibiting its inactivation, and that have proved useful in several animal models of pain, inflammation, and itch (15,16,(41)(42)(43)(44)(45)(46)(47)(48), might not be necessarily suitable for the symptomatic treatment of candidiasis, as they might also promote the formation of 3-HAEA, a likely algogenic compound. Furthermore, our data provide an unusual example of the typical capability of pathogenic microorganisms to control, or even exploit, innate defense mechanisms to facilitate infection (49,50).…”
Section: Discussionmentioning
confidence: 99%
“…TRPV1 sensitization likely occurs during candidiasis, because increased expression of vulvar TRPV1 receptors is observed during vulvodynia, a condition similar to that caused by candidiasis (14), and clotrimazole, a widely used antimycotic agent, was suggested to owe its inflamma- tory and algogenic side effects to its capability to activate TRPV1 receptors (40). On the other hand, several peripheral inflammatory conditions causing pain and/or itch are known to be accompanied by elevated levels of anandamide as an adaptive reaction to counteract these symptoms, as suggested by the observation that compounds that prolong the life span of anandamide by inhibiting its inactivation exert anti-inflammatory effects (15,16,(41)(42)(43)(44)(45)(46)(47). Thus, it seems reasonable to hypothesize that, during candidiasisinduced inflammation, on the one hand TRPV1 is sensitized, and, on the other hand, anandamide is produced by host or neighboring cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation